Ναυτιλιακοί κύκλοι και χρηματοδότηση ναυτιλιακών επενδύσεων - Τρύφωνος, Δημήτρης (Τμήμα Εμπορίου, Χρηματοοικονομικών και Ναυτιλίας, Σχολή Διοίκησης και Οικονομίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
This study addressed the issue of the industry and financing shipping investments and completed through seven chapters, which particularly in the first chapter mentioned during shipping circles indicating the stages thereof. Then the second chapter made reference about shipping circles examining each period separately in each cycle from 1966 until 2008. Then, the third chapter talked about the demand and supply in the sector, focused on shipping pointers made provisions and referred to the role of investors in the market and investors during the shipping cycle. The fourth and fifth chapters were description of data and the research methodology in which was recorded information about the manner in which the investigation was conducted and the statistical analysis was made. The sixth chapter and final was the empirical analysis where research and statistical analysis was performed. Finally, the assignment ended with conclusions.
Keywords: Marine cycles; Marine indicators; Trade; Demand; Supply; Investment; Ναυτιλιακοί κύκλοι; Ναυτιλιακοί δείκτες; Εμπόριο; Ζήτηση; Προσφορά; Επενδύσεις